A tangled web: views of deception from the customer's perspective. (26th June 2014) - Gillespie, Erin Adamson; Hybnerova, Katie; Esmark, Carol; Noble, Stephanie M.
Abstract : While there has been extensive research on deception, extant literature has not examined how deception is processed solely from the customer's perspective. Extensive qualitative interviews were conducted and analyzed to inform the proposed framework. Cognitive dissonance theory and attribution theory are used to frame the process consumers go through when deception is perceived. When consumers perceive deceit, they will consider attribution before determining intentionality. Internal attributions relieve the company of wrongdoing to some extent, whereas external attributions lead consumers to examine several elements of deception including intent. Unintentional deceit will trigger assessments of magnitude, stability, and switching costs; while less is considered when deceit is intentional. The findings of this research are important for advancing theory in relation to deceit and for helping practitioners understand the importance of changing consumer cognitions before consumers decide to change their behavior by discontinuing the relationship.